Mosquito larvae detection using deep learning - Asmai, Siti Azirah; Mohamad Zukhairin, Mohamad Nurallik Daniel; Mohamad Jaya, Abdul Syukor; Abdul Rahman, Ahmad Fadzli Nizam; Abal Abas, Zuraida (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
Dengue cases has become endemic in Malaysia. The cost of operation to exterminate mosquito habitats are also high. To do effective operation, information from community are crucial. But, without knowing the characteristic of Aedes larvae it is hard to recognize the larvae without guide from the expert. The use of deep learning in image classification and recognition is crucial to tackle this problem. The purpose of this project is to conduct a study of characteristics of Aedes larvae and determine the best convolutional neural network model in classifying the mosquito larvae. 3 performance evaluation vector which is accuracy, log-loss and AUC-ROC will be used to measure the model’s individual performance. Then performance category which consist of Accuracy Score, Loss Score, File Size Score and Training Time Score will be used to evaluate which model is the best to be implemented into web application or mobile application. From the score collected for each model, ResNet50 has proved to be the best model in classifying the mosquito larvae species